Meat Inspection And Cultural Isolation Of mycobacteriaas predictors Of Bovine Tuberculosis In Ibadan (2007)
ln order to asccnain the elTectiveness of meat inspection as against the conventional culture method in the confirmation of tubercuiosis in caltle slaughtered at Bodija abattoir. Ibadan; a study to assess these two methods in their abilitv to diagnose bovine tubercuiosis was carried out. In all. 290 cattle were inspected at the abattoir out of vvhich 182 had miliary nodules and granulomatous tubercles in the different organs and their associated lymph nodes vvhich are suggestive of tubercuiosis. One hundred and fifty-nine (54.8%) animals were confirmed to have tubercuiosis based on the mycobacterial culture. The sensitivity and speciftcity results of the postmortem examination vis-a vis the culture were 100% and 82.4% respectively; vvhile the Positive Predictive Value (PPV) and the Negative Predictive Value (NPV) were 87.4% and 100% respectively. This study therefore confirms that vvith proper meat inspection. a large proporlion of tuberculous cattle can be identified at postmortem. Hence. more emphasis should be directed at the improvement of meat inspection Services in Nigeria since there are no availabTe laboratory facilities for the diagnosis of bovine tubercuiosis in the abattoirs.